Legal Analysis of Red Notices in the Handling of Wanted Persons (DPO) Cases in Indonesia: A Study Based on Law No. 1 of 1979 on Extradition (Articles 2, 3, 4, 5), and Police Regulation No. 1 of 2020 on the Functions of the NCB -Interpol Indonesia, with the Case of Fugitive Former Investree CEO Adrian Gunadi as the Focus - Idrus, Nabain; Bunyamin, Ilham Akbar; Andiani, Paramita (West Science Law and Human Rights, 2025)
This study examines the legal framework and implementation of Red Notices in handling fugitive cases (Daftar Pencarian Orang – DPO) in Indonesia, with a particular focus on the case of the former CEO of Investree, Adrian Gunadi. Using a normative legal analysis, the research explores the application of Law Number 1 of 1979 concerning Extradition (Articles 2, 3, 4, and 5) and Police Regulation Number 1 of 2020 concerning the Functions of the NCB–Interpol Indonesia. The findings reveal that the Red Notice serves as a crucial tool for international law enforcement cooperation but lacks the status of a binding arrest warrant under Indonesian law. Its execution depends on the harmonization between national legal sovereignty and international obligations. The study also identifies legal and institutional challenges, such as procedural inconsistencies, limited inter-agency coordination, and inadequate bilateral extradition treaties, which hinder effective implementation. The case of Adrian Gunadi highlights these weaknesses, demonstrating the need for stronger regulatory mechanisms, enhanced cooperation between NCB–Interpol Indonesia and foreign counterparts, and policy reforms to ensure due process and accountability. Overall, this research underscores the importance of integrating Red Notice practices into Indonesia’s legal framework to improve the pursuit and extradition of fugitives within the boundaries of both domestic and international law.